Mutation rate at 13 rapidly mutating Y-STR loci in the population of Serbia. (December 2017) - Zgonjanin, Dragana; Alghafri, Rashed; Almheiri, Reem; Antov, Mirjana; Toljic, Danka; Vukovic, Radenko; Petkovic, Stojan
Abstract: Recently, the interest of the forensic community has been focused on new Y-chromosomal short tandem repeats (Y-STRs), termed Rapidly Mutating Y-STRs (RM-YSTRs), which is able to differentiate between close males belonging to the same paternal lineage due to their high mutation rates. In this study, we have estimated a mutation rate for 13 RM-YSTR in 85 pairs of male relatives in the population of Serbia. We analysed 74 father-son pairs, and 11 twin pairs, to evaluate the capacity of distinguishing between male subjects within a single lineage. Each father-son couple was previously confirmed by autosomal STRs testing (AmpFℓSTR ® Identifiler Plus™ kit, Applied Biosystems) with paternity probability ≥99.99% and also confirmed monozygotic or dizygotic twins. Results showed that, in the 74 father-son pairs 23 mutations were detected of which 22 were one-step mutations and 1 was two-step mutation, while in the 11 twin pairs 1 mutation was observed in one dizygotic twin pair. Five father-son pairs were found to have mutations at two loci, while one pair at four loci. Overall, the most mutable markers were DYF399S1, DYF387S1, DYF403S1a and DYS612. Our findings are encouraging and concur with previous studies showing that by RM-YSTR typing the discrimination power of male relatives could be considerably increased in comparison to every YSTR markers commonly used in forensic genetics.